The influence of custom-milled framework design for an implant-supported full-arch fixed dental prosthesis: 3D-FEA sudy - Tribst, João Paulo Mendes [UNESP] (2020)
The current study aimed to evaluate the mechanical behavior of two different maxillary prosthetic rehabilitations according to the framework design using the Finite Element Analysis. An implant-supported full-arch fixed dental prosthesis was developed using a modeling software. Two conditions were modeled: a conventional casted framework and an experimental prosthesis with customized milled framework. The geometries of bone, prostheses, implants and abutments were modeled. The mechanical properties and friction coefficient for each isotropic and homogeneous material were simulated. A load of 100 N load was applied on the external surface of the prosthesis at 30° and the results were analyzed in terms of von Mises stress, microstrains and displacements. In the experimental design, a decrease of prosthesis displacement, bone strain and stresses in the metallic structures was observed, except for the abutment screw that showed a stress increase of 19.01%. The conventional design exhibited the highest stress values located on the prosthesis framework (29.65 MPa) between the anterior implants, in comparison with the experimental design (13.27 MPa in the same region). An alternative design of a stronger framework with lower stress concentration was reported. The current study represents an important step in the design and analysis of implant-supported full-arch fixed dental prosthesis with limited occlusal vertical dimension.